Cardiovascular responses to microinjections of GABA or anesthetics into the rostral ventrolateral medulla of conscious and anesthetized rats - Lacerda J.E.C. (Brazilian Journal of Medical and Biological Research, 2003)
The rostral ventrolateral medulla (RVLM) contains neurons involved in tonic and reflex control of arterial pressure. We describe the effects of gamma-aminobutyric acid (GABA) and anesthetics injected into the RVLM of conscious and urethane (1.2 g/kg, iv) anesthetized Wistar rats (300-350 g). In conscious rats, bilateral microinjection of GABA (50 nmol/200 nl) induced a small but significant decrease in blood pressure (from 130 ± 3.6 to 110 ± 5.6 mmHg, N = 7). A similar response was observed with sodium pentobarbital microinjection (24 nmol/200 nl). However, in the same animals, the fall in blood pressure induced by GABA (from 121 ± 8.9 to 76 ± 8.8 mmHg, N = 7) or pentobarbital (from 118 ± 4.5 to 57 ± 11.3 mmHg, N = 6) was significantly increased after urethane anesthesia. In contrast, there was no difference between conscious (from 117 ± 4.1 to 92 ± 5.9 mmHg, N = 7) and anesthetized rats (from 123 ± 6.9 to 87 ± 8.7 mmHg, N = 7) when lidocaine (34 nmol/200 nl) was microinjected into the RVLM. The heart rate variations were not consistent and only eventually reached significance in conscious or anesthetized rats. The right position of pipettes was confirmed by histology and glutamate microinjection into the RVLM. These findings suggest that in conscious animals the RVLM, in association with the other sympathetic premotor neurons, is responsible for the maintenance of sympathetic vasomotor tone during bilateral RVLM inhibition. Activity of one or more of these premotor neurons outside the RVLM can compensate for the effects of RVLM inhibition. In addition, the effects of lidocaine suggest that fibers passing through the RVLM are involved in the maintenance of blood pressure in conscious animals during RVLM inhibition.